Penerapan Algoritma Genetika untuk Traveling Salesman Problem dengan Menggunakan Metode Order Crossover dan Insertion Mutation - Samuel Lukas; Toni Anwar; Willi Yuliani (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
Traveling Salesman Problem is one of the most famous optimization problem and genetic algorithm is themost famous optimization problem solver. This paper demonstrates how the genetic algorithms can solve thisTraveling Salesman Problem effectively. The four variables of genetic algorithm that are number ofchromosomes, number of generations, crossover probability and mutation probability are set in such a way tosolve the problem.Kata kunci: Traveling Salesman Problem, genetic algorithm, optimization